P303 Exploring attitudes to virtual gastroenterology clinic provision: a patient survey. (19th June 2022) - Abeysekera, Kushala; Saunsbury, Emma; Sheiybani, Giovanna; Belfield, Katherine; Lin, Simeng; Pohl, Keith; Wesley, Emma
Abstract : Introduction: The COVID-19 pandemic has forced patients to rapidly adjust to virtual consultations in outpatients. A perceived benefit is reducing unnecessary travel. However, there is a paucity of literature describing acceptability of virtual consultations to gastroenterology patients. Methods: In collaboration with the Patient Experience team, satisfaction surveys were disseminated in Gastroenterology and Hepatology clinics at Bristol Royal Infirmary electronically via SurveyMonkey® and paper format between June and August 2021. These consisted of multiple choice questions and Likert 5-scale ranking questions, ranging from 'strongly agree' to 'strongly disagree'. Virtual clinics were defined as telephone or video consultations. Data was collected on patient demographic, travel method, satisfaction with virtual clinics, and preferences for service delivery. Results: 100 patients completed the survey (27% aged 55-64yrs; 21% aged 65-74 years). 50%, 27% and 23% of patients were from hepatology clinic, inflammatory bowel disease clinic and general gastroenterology clinic respectively. 84% were follow-up patients. 56% of patients normally drove to appointments, with a further 30% taking public transport. 23% of patients were travelling over 10 miles to attend appointments. 38% of patients were in full-time employment of which 63.1% had to take annual leave to attend appointments (n=24/38). 82% of patients owned a laptop of which 19.5% (n=16/82) disagreed or strongly disagreed with feeling comfortable using their computer for an online appointment. Face-to-face (F2F) consultation was the preferred mode of appointments in almost half of patients (49%), followed by a mix of F2F and telephone consultations (19%). 54% of patients agreed or strongly agreed that clinicians could address their concerns virtually, with only 16% disagreeing or strongly disagreeing with this. 65% of patients agreed or strongly agreed they felt comfortable sharing personal information during a virtual consultation, with 14% of patients disagreeing or strongly disagreeing with this. 80% of patients stated they would want to receive bad news in a F2F consultations. Conclusions: Virtual consultations appear to be acceptable rather than preferable to gastroenterology patients. F2F consultations remain the overall preference, particularly when receiving bad news. Virtual consultations can provide flexibility in service delivery. This is important given almost two thirds of patients in full time employment had to take annual leave to attend an appointment. Furthermore, as services consider their carbon footprint, with half of patients driving to their appointments in Bristol, virtual consultations offer a genuine opportunity to provide a greener service.